Ossification of Caroticoclinoid Ligament in a Human Skull: A Case Report - Masoud Ghorbani; Gholamreza Dashti (Negah Institute for Scientific Communication, 2020)
Introduction: The Anterior clinoid process (ACP) and middle clinoid process (MCP) are sometimes connected by an osseous bridge formed by the ossification of caroticoclinoid ligament (CCL), converting the distal end of the carotid sulcus into an ostium called the caroticoclinoid foramen (CCF). The internal carotid artery (ICA) passes through this foramen, which is developed due to the ossification of either the caroticoclinoid ligament or a dural fold present between anterior and middle clinoid processes and occasionally connecting posterior clinoid process (PCP) of the sphenoid bone. The presence of a bony CCF may compress ICA, leading to clinical implications by increasing the risks of ischemic and neurological disorders during surgical access by neurosurgeons. It may also affect the hypothalamus or induce neurological problems by compressing optic or oculomotor nerves, causing hormonal imbalances, visual problems, headache, behavioral changes, etc. Regarding the clinical significance of CCF, this study aimed to evaluate the anatomical relationship and morphology of the CCF to plan a safe and successful surgery on the middle cranial fossa. Methods: The presence of ossified CCL was noticed in a dry human skull. The morphometry was performed by a manual caliper, and the detailed measurements of the CCL, CCF, ACP, and MCP dimensions were performed and recorded. Results: Considering these facts, detailed anatomical knowledge of this region is of clinical importance for neurosurgeons, neurophysicians, endocrinologists, and radiologists for radiological evaluations of the CCL and its treatment in the middle cranial fossa. Conclusion: The growing awareness of differences in anatomical landmarks in the skull base can support the diagnosis and treatment of clinical complications related to the parasellar region.